Rethinking Recollection and Plato's Theory of Forms. - Schumacher, Lydia (Lyceum, 2010)
The article discusses the essentialists' interpretation on recollection and Plato's theory of forms to retrieve the realm of immutable being. It explores several literary works of Plato which show the philosopher's knowledge of forms including "Phaedo," "Phaedrus," and "Euthyphro." It features essentialists Lloyd Gerson and Nicholas White comments on Platonic forms. It is stated that although these interpretations and understanding of recollection is uncontested, it is not the standard in the history of philosophy.